KAJIAN TRANSFORMASI VISUAL ARSITEKTUR WEDDING CHAPEL DAN PERANNYA TERHADAP INDUSTRI PARIWISATA BERKELANJUTAN DI BALI - Swari, Ni Luh Gede Niti (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Abstract Bali Island is one of the most popular tourism destinations in the world. Apart from being famous for its natural beauty especially its beaches, Bali also famous for its unique and interesting arts and culture. These things makes Bali as a place for a wedding venue. Bali provides a lot of wedding chapels that have different visual forms and concepts. Supported by the natural beauty, exotic scenery, the existence of Wedding Chapel facilities and various attractive wedding packages ,now Bali Island is now also becoming a popular Wedding Venue destination in the world. So that many domestic and foreign tourists come to Bali to get married. Most of the Wedding Chapel in Bali has visual architectural forms and concepts that contrast with Balinese Traditional Architecture. Of course these things gives new color for Balinese Architecture that we have known so far with its traditional Balinese viscosity. Based on this phenomenon, this research was held to examine the visualization transformation of the Wedding Chapel architecture in Bali using descriptive analysis research methods. The results obtained in the form of studies that illustrate the visualization of Wedding Chapel architecture in terms of its form and function. With the existence of these Wedding Chapel facility, it is expected to be able to support the sustainability of the tourism industrial development of the Bali Island. Keywords: Wedding Chapel, Visual Architecture, Sustainability Tourism.